Integration of Islamic Law in Global Trade Transactions in The Digital Era; Normative and Comparative Study - Tjahjana Budiman (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2025)
Digital-based global trade has transformed cross-border transactions into an ecosystem that relies on electronic contracts, online marketplaces, fintech payment channels, algorithmic mediation, and cross-jurisdictional data flows. This transformation raises legal issues regarding the validity of agreements, Sharia compliance, consumer protection, data governance, platform accountability, and cross-border enforceability. This undergraduate legal research examines the integration of Islamic law in global trade transactions in the digital era through normative and comparative approaches. This study analyses muamalah principles, particularly the prohibitions on riba (usury), gharar (uncertainty), and maysir (gambling), and uses maqasid al-sharia as an evaluative framework to assess whether digital trade practices protect property, honour, and justice (Al-Shatibi, 2004). The analysis is compared with Indonesian positive law governing the digital economy, including Government Regulation Number 80 of 2019 concerning Trade Through Electronic Systems, Law Number 1 of 2024 as the second amendment to the Electronic Information and Transactions regime, Law Number 27 of 2022 concerning Personal Data Protection, and Law Number 8 of 1999 concerning Consumer Protection (Republic of Indonesia, 1999; 2019; 2022; 2024). This research also aligns Sharia norms with international instruments that facilitate the recognition of cross-border electronic communications based on functional equivalence, namely the UNCITRAL Model Law on Electronic Commerce and the UN Convention on Electronic Communications in International Contracts (UNCITRAL, 1996; United Nations, 2005). A comparative study of literature indexed in Google Scholar, SINTA, and Scopus shows that previous research often positioned Sharia compliance as a conceptual checklist, while recent Scopus studies emphasize the importance of trust, governance, and institutional design as prerequisites for a Sharia-compliant digital ecosystem (Ribadu & Rahman, 2019; Wira, 2024). This research offers a layered integration model that connects Sharia contract compliance, national regulatory compliance, technological accountability, and cross-border dispute resolution. The results conclude that Islamic law is normatively compatible with global digital trade as long as the principles of transparency, halal objects, informed consent, justice, and accountability are upheld through executable legal and governance mechanisms.